5 Cervical Spine Pedicle Screw Accuracy in Open Fluoroscopic, Navigated and Template Guided Systems- a Systematic Review. (28th February 2022) - Mahmoud, A.; Aly, M.; Shanmuganathan, K.; Rocos, B.; Sedra, F.; Montgomery, A.; Aftab, S.
Abstract: Aim: Pedicle screws provide excellent fixation for a wide range of indications; their adoption in the cervical spine has been slower than in the thoracic and lumbar spine, largely due to the smaller pedicle sizes and proximity to neurovascular structures in the neck. Recent years have seen the development of technology to improve accuracy and thereby safety in cervical pedicle screw placement over traditional fluoroscopic techniques, including intraoperative 3D navigation, computer assisted systems and physical templates with screw guides. We have performed a systematic review into the accuracy rates of the various systems. Method: PubMed and Cochrane Library databases were searched; keywords "pedicle screw cervical spine" were searched; 9 valid papers involving 1427 screws were found. Results: Accuracy rates were 80.6% for fluoroscopy, 91.4% for navigation methods, and 96.7% for templates. Conclusions: Superior results for templates are complemented by reduced radiation exposure to patient and surgeon; however, the technology requires prolonged pre-operative planning to create the bespoke template, and the development of an infrastructure to allow for their rapid production and delivery is needed before they become more widely available. Two broad methods of navigation currently exist: intraoperative CT scanning providing real-time 3D navigation and preoperative CT registration in relation to a fixed reference with intraoperative computer assistance. At present, these methods are more commonly used, due to their proven improved accuracy rates over fluoroscopy, availability in emergencies and alongside minimally invasive techniques. Despite their novelty and limitations, templates provide promising accuracy scores, although practical considerations may inhibit their proliferation.